Information Security Readiness Assessment at XYZ Agency Using KAMI Index 4.2 - Afriyani, Febrilia Dinda; Rahayu, Risgi Sri (Universitas Ahmad Dahlan, 2024)
Dinas Xyz is an agency owned by the government of the Special Region of Yogyakarta (DIY) Province. This agency is responsible for managing activities in a region. This research was conducted to evaluate the level of information security readiness at Dinas Xyz using the KAMI Index 4.2 based on ISO/IEC 27001:2013 criteria. This research involves data collection through interviews and observations, followed by data analysis using the KAMI Index categories. The results showed that Dinas Xyz has a sufficient level of information security readiness, with a score of 285 out of a total of 645. This article provides details of the evaluation results for each category. This research suggests improvements to information security management, especially on cloud storage, to meet the minimum requirements of ISO.